Hubungan Antara Tingkat Pendidikan dengan Kejadian Diabetes Melitus Tipe II - Jigibalom, Ance; Podung, Beatrix J; Sudirham, Sudirham (Yayasan Syalom Cipta Sumikolah, 2025)
Diabetes mellitus (DM) is a disease that poses a public health problem. Diabetes mellitus is listed as the fourth national research priority for degenerative diseases. Type II diabetes mellitus was among the ten most prevalent diseases in the Koya Tondano Community Health Center work area, with a total number of sufferers in 2016. The increase in the number of diabetes sufferers is also caused by risk factors, one of which is risky health behavior. Education level also plays a role in the increase in this disease. Education level usually influences health behavior. This study aims to examine the relationship between education level and the incidence of type II diabetes in the Koya Tondano Community Health Center work area. This study used an observational analytical study with a cross-sectional study design. The population used in this study was the average number of patients visiting the Koya Tondano Community Health Center in 2022, namely 161 people. The sampling technique in this study was purposive sampling with a sample size of 115 based on the Yamen formula. The results showed that the majority of respondents (81 people) had a high level of education, while 34 (29.6%) had a low level of education. Of the respondents who had diabetes at the time of the study, 40 (34.8%) had diabetes, while 75 (65.2%) did not have diabetes. Bivariate analysis showed a relationship between education level and the incidence of diabetes mellitus in the Koya Community Health Center, South Tondano District, with a P value of 0.026.